Optimal currency area and anchor currency in Southeast Asia - Thanarerk Thanakijsombat (2018)
© 2016 Inderscience Enterprises Ltd. This study examines the feasibility of the OCA formation and the selection of optimal anchor currency in ASEAN. Following the generalised purchasing power parity (G-PPP) framework, modern cointegration tests are employed on bilateral exchange rates involving ASEAN-5 currencies against four currencies of ASEAN's top trading partners during 2003-2014. The findings reveal that ASEAN members are not ready to form an OCA, as only a few significant bivariate and inconclusive multivariate cointegrating relationships can be found. With the eventual goal of forming a currency union, ASEAN policy makers may need to initially pursue bilateral economic and monetary integration led by Malaysia before extending the effort to the whole region. Significant long-run multivariate linkages among ASEAN currencies reveal no dominant anchor currency within the region, possibly due to the indifferent levels of trades and investments between ASEAN and each major trading partner. Lastly, endogenously determined break dates coincide with the 2008 global financial crisis (GFC) and reveal that ASEAN members may be affected by and may respond to the crisis at different timings, suggesting that past studies regarding ASEAN OCA may suffer from break-date selection bias.